A southerly wind event and precipitation in Ny Ålesund, Arctic. (May 2022) - Nuncio, M.; Satheesan, K.; Acharya, Asutosh; Chatterjee, Sourav; Subeesh, M.P.; Athulya, R.
Abstract: Precipitation in the Arctic is expected to increase with implications to ecosystems and changes to atmospheric circulation. In the Arctic strong southerly wind, often known as atmospheric rivers, supply enormous moisture and heat into the Arctic and is expected to increase in future warming scenarios. The impact of these events on Arctic climate change is not yet understood fully. In this study precipitation associated with such an event is studied for Ny Ålesund, Svalbard for 2016 March. During the event, the high precipitation was noticed between 22 and 23 UTC and 6–9 UTC on 12th March and 13th March respectively. It has been shown that during these two time periods, downwelling longwave radiation increased due to clouds. The enhanced downwelling longwave radiation increased the surface temperature locally. Above the shallow planetary boundary, advection dominated the temperature changes and initiated a shallow convection in the atmosphere leading to intensified precipitation in the lower layers during the event. Enhanced vertical velocity in MRR could be a result of this convection. Thus, the largescale southerly winds, that developed into an atmospheric river has not only contributed to the supply of heat and moisture but also enhanced cloud radiative effects and resulted in local warming. The moisture sources for this event appears to be Norwegian Sea and the east coast of Greenland. The scenario we have investigated was characterised by a warm Arctic with southerly warm winds. Studies suggest that convective scale precipitation is increasing in Eurasia under warm conditions. Our study points to the change in precipitation regime that Arctic may characterise as the warming continues. Highlights: Northward transports associated with large scale atmosphere circulation impacted Arctic precipitation and temperature in March 2016. During the second week of March 2016 an atmospheric river was noticed over the North Atlantic. Enhanced temperature and precipitation were associated with this in Ny Alesund, Arctic. Advection by atmospheric river warmed the atmosphere and initiated a shallow convection above the planetary boundary layer. Below the planetary boundary layer the warming was due to cloud radiative effects.